Application and implementation of a number of methods of cold hydrothermal processing of grain products at flour milling enterprises. - Akramova Gulhayo (Genius Journals, 2023)
in this article, to improve the quality of grain during its processing and proper processing, the quality of the grain product is used, and for the process of moistening and steaming flour, the use of cold and hot air conditioning, which improves the quality of flour and saves time
Keywords: Grain; hot and cold conditioning; grain processing; humidity